Comparing Diagnostic-Driven Approaches to Empiric Therapy in the Treatment of Invasive Aspergillosis in Patients with Hematologic Malignancy. (4th October 2017) - Dib, Rita Wilson; Chaftari, Anne-Marie; Ghaly, Fady; Jiang, Ying; Hachem, Ray Y; Raad, Issam
Abstract: Background: Early antifungal therapy of invasive aspergillosis (IA) has been shown to be associated with improved outcome. Given the difficulty to establish the diagnosis of IA based on conventional methods, early initiation of empiric antifungal therapy has been used in patients with clinically suspected IA. Diagnostic-driven approach (DDA) relies on using novel diagnostic methods (e.g., early galactomannan testing). In this current study, we compared the outcomes of hematological malignancy (HM) patients with IA who were treated with Voriconazole using the DDA (DDA-Vori) vs. empiric therapy with a non-Voriconazole containing regimen (EMP-non-Vori) or empiric therapy with Voriconazole (EMP-Vori). Methods: We retrospectively reviewed the medical records of 604 HM patients with documented, proven or probable IA (according to EORTC/MSG criteria) diagnosed between July, 1993 and February, 2016 at our center. We included 346 patients with underlying host factors, a suggestive CT findings of IA, and positive biopsy, fungal culture or galactomannan indicative of IA, and who received at least 7 days of DDA-Vori, EMP-Vori, or EMP-non-Vori. Outcome assessment included response to therapy (clinical and radiographic), all causing mortality and IA attributable mortality. Results: The patients' median age was 54 years and 59% were males. By multivariate analysis, factors that were predictive of a favorable response included: localized/sinus IA vs. disseminated/pulmonary IA ( P < 0.0001), not receiving WBC transfusion ( P < 0.01), and DDA-VORI vs. EMP-non-Vori ( P < 0.0001). On the other hand, predictors of mortality within 6 weeks of initiation of IA therapy included disseminated/pulmonary infection vs. localized/sinus IA ( P < 0.01), not having stem-cell transplant within 1 year prior of IA ( P = 0.01) and EMP-non-Vori vs. DDA-Vori ( P < 0.001). Conclusion: DDA-Vori is associated with a better outcome (response and survival) when compared with EMP-non-Vori and equivalent outcome to EMP-Vori. The superior to equivalent outcome associated with the DDA approach could also reduce unnecessary costs and adverse events associated with widespread use of empiric therapy. Disclosures: I. Raad, Merck: Grant Investigator, Research grant. Allergan: Grant Investigator, Research grant. Infective Technologies, LLC: Co-Inventor of the Nitroglycerin-Citrate-Ethanol catheter lock solution technology which is owned by the University of Texas MD Anderson Cancer Center (UTMDACC) and has been licensed by Novel Anti-Infective Technologies, LLC in which Dr. Raad is a s and Shareholder, Licensing agreement or royalty